Small-strain folding of semi-rigid elastomer derives high-performance 3D-printable soft origami actuators - Liu, Sicong; Chen, Fang; Duanmu, Dehao; Wang, Yaxi; Liu, Jianhui; Yang, Wenjian; Zhu, Yuming; Wu, Yige; Yi, Juan; Dai, Jian S.; Wang, Zheng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •The approach of using semi-rigid elastomer to create soft actuator is proposed.•Small-strain folding (SSF) of the origami structure is utilized to generate motion.•Fabrication by Selective Laser Sintering printing with post-treatment is obtained.•Achieve superior performance in lifespan, linearity, energy efficiency, and force.•The SSF actuators benefit the development of soft robots and their performance. Elastomers with hyperelastic deformation bring prosperity to soft robotics, especially in constituting fluidic actuators, largely due to the merit of large deformation and airtightness. However, the large (typically 0.5–1.5 strain) in-plane stretching of such materials concurrent to motion generation inevitably causes energy loss, hinders force output and accuracy. Particularly, the high nonlinearity of the low-durometer (typically 10A to 30A Shore) hyperelastic elastomers makes the modeling and control of actuators a well-known challenge. In this work, we proposed an alternative approach of using semi-rigid elastomer of significantly larger durometer (70 A–100 A) to create the typical fluidic soft actuator with axial translation, by utilizing small-strain folding to generate motion. Deformation constraints and property programming are combined into a single-piece body, enabling easy fabrication by Selective Laser Sintering 3D-printing and post-treatment for origami patterned structure. Systematic analyses on the principles, modeling and design are presented. The long lifespan (over 1 million cycles), superior output linearity, high energy efficiency (more than 60% increase), and drastically improved force output (more than 98% increase) were validated experimentally, showing high potentials in enabling high-performance soft actuators that are easy to design, fabricate and drive, strong to use, and accurate to control, towards even wider applications.